3D electron diffraction techniques - Gemmi, Mauro; Lanza, Arianna E (Acta crystallographica. Section B, Structural science, 2019)
3D electron diffraction is an emerging technique for the structural analysis of nanocrystals. The challenges that 3D electron diffraction has to face for providing reliable data for structure solution and the different ways of overcoming these challenges are described. The route from zone axis patterns towards 3D electron diffraction techniques such as precession‐assisted electron diffraction tomography, rotation electron diffraction and continuous rotation is also discussed. Finally, the advantages of the new hybrid detectors with high sensitivity and fast readout are demonstrated with a proof of concept experiment of continuous rotation electron diffraction on a natrolite nanocrystal.